Dominant Allele Phylogeny and Constitutive Subgenome Haplotype Inference in Bananas Using Mitochondrial and Nuclear Markers. (27th August 2017) - Muiruri, Kariuki Samwel; Britt, Anne; Amugune, Nelson Onzere; Nguu, Edward; Chan, Simon; Tripathi, Leena
Abstract: Cultivated bananas ( Musa spp.) have undergone domestication patterns involving crosses of wild progenitors followed by long periods of clonal propagation. Majority of cultivated bananas are polyploids with different constitutive subgenomes and knowledge on phylogenies to their progenitors at the species and subspecies levels is essential. Here, the mitochondrial ( NAD1 ) and nuclear ( CENH3 ) markers were used to phylogenetically position cultivated banana genotypes to diploid progenitors. The CENH3 nuclear marker was used to identify a minimum representative haplotype number in polyploids and diploid bananas based on single nucleotide polymorphisms. The mitochondrial marker NAD1 was observed to be ideal in differentiating bananas of different genomic constitutions based on size of amplicons as well as sequence. The genotypes phylogenetically segregated based on the dominant genome; AAB genotypes grouped with AA and AAA, and the ABB together with BB. Both markers differentiated banana sections, but could not differentiate subspecies within the A genomic group. On the basis of CENH3 marker, a total of 13 haplotypes (five in both diploid and triploid, three in diploids, and rest unique to triploids) were identified from the genotypes tested. The presence of haplotypes, which were common in diploids and triploids, stipulate possibility of a shared ancestry in the genotypes involved in this study. Furthermore, the presence of multiple haplotypes in some diploid bananas indicates their being heterozygous. The haplotypes identified in this study are of importance because they can be used to check the level of homozygozity in breeding lines as well as to track segregation in progenies.